A longitudinal investigation of IFRS-8 implementation: evidence from Qatar. (25th January 2023) - Mardini, Ghassan H.; Alkurdi, Amneh; Ahmed, Ahmed Hassan
The main objective of the current study is to investigate the segmental information reporting (SIR) of Qatari listed firms covering the period from 2009 to 2018. The sample comprises all companies listed on the Qatar Stock Exchange (QSE) at the end of 2009. A disclosure index was developed to determine the extent of SIR amongst the sample companies. The study used a longitudinal empirical analysis approach; a year-by-year analysis. The findings revealed a gradual upsurge and awareness of the requirements of IFRS-8 from year to year. Moreover, the reported results suggest that the post-implementation review of IFRS-8 has had a large and positive impact on SIR disclosures since 2014. This research should provide substantive insights for regulators and standard-setters in identifying best practices and spreading awareness of SIR, which in turn should allow SIR practices to become more standardised, making them easier to monitor and govern. Our study provides a longitudinal examination of segmental reporting practices in a developing country, such as Qatar, which permits direct examination of the progress made regarding the implementation and extent of SIR.